2022
DOI: 10.1021/acsaem.2c02906
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic Framework-Derived CoSx/NiS Co-Decorated Heterostructures: Toward Simultaneous Acceleration of Charge Carrier Separation and Catalytic Kinetics

Abstract: Designing semiconductor-based heterojunctions for achieving high-efficiency electron–hole separation and rapid catalytic kinetics is highly important for promoting photoelectrochemical water oxidation performance. Herein, we synthesize a dual-cocatalyst-decorated heterostructure (TiO2/CdS/CoSx/NiS) via in situ metal–organic framework (MOF) derivation. The homogeneous dispersion of CoSx/NiS, benefiting from the MOF derivation of atomic metal building blocks, significantly accelerates the catalytic kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For the past few years, hollow porous metal–organic framework (MOF) materials have aroused great research interest due to their unique structure and properties, particularly their high surface area. MOF derivatives realized through simple oxidation or vulcanization with distinct morphological structures that expose more surface active sites are ideal photocatalytic carriers. , For instance, Ma et al demonstrated that the CoS x hollow nanocage derived from ZIF-67 (a type of Co-containing MOF) not only enhances light energy absorption and shortens the transfer path of photogenerated carriers but also provides abundant surface active sites for photocatalytic reactions, owing to its distinctive cavity structure and large specific surface area. Currently, numerous reports focus on photocatalytic hydrogen production using CoS x -based nanocomposites; however, there is a scarcity of research regarding the photocatalytic degradation of pollutants by CoS x -based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, hollow porous metal–organic framework (MOF) materials have aroused great research interest due to their unique structure and properties, particularly their high surface area. MOF derivatives realized through simple oxidation or vulcanization with distinct morphological structures that expose more surface active sites are ideal photocatalytic carriers. , For instance, Ma et al demonstrated that the CoS x hollow nanocage derived from ZIF-67 (a type of Co-containing MOF) not only enhances light energy absorption and shortens the transfer path of photogenerated carriers but also provides abundant surface active sites for photocatalytic reactions, owing to its distinctive cavity structure and large specific surface area. Currently, numerous reports focus on photocatalytic hydrogen production using CoS x -based nanocomposites; however, there is a scarcity of research regarding the photocatalytic degradation of pollutants by CoS x -based nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…18 Moreover, Li et al synthesized NiS-modified heterojunction photocatalysts to remarkably promote the water-splitting performance, in which the NiS cocatalyst significantly accelerates the separation of electron–hole pairs and simultaneously promotes the surface catalytic reaction of the host photocatalyst. 20 Moreover, the research reported by Zhang et al suggests that the BiVO 4 /NiS/Au photocatalyst presents a noticeable improvement of the photodegradation efficiency by accelerating the interfacial O 2 -reduction process compared with that of pure BiVO 4 . 21 Based on the above results reported in the literature, NiS is proved to become a potential and high-efficiency cocatalyst for adjusting the adsorption form of O 2 on the surface of the photocatalyst and accelerating the photocatalytic O 2 reduction reaction.…”
Section: Introductionmentioning
confidence: 99%